Learning Cultural Arts (Music) in Class VIII 3 SMPN 2 Koto XI Tarusan - Azidan, Ramadandi; Marzam (Avant-garde: Jurnal Ilmiah Pendidikan Seni Pertunjukan, 2024)
The purpose of this research is to identify and explain how the implementation of Cultural Arts learning with the material of Indonesian Traditional Musical Instruments in class VIII 3 SMPN 2 Koto XI Tarusan takes place. This research is included in the type of qualitative research that uses a descriptive approach. Researchers use themselves as research instruments, as well as stationery and cameras as a means of data collection. Data were collected through observation, interview, and documentation. The data analysis process includes data classification, data clarification, data analysis, data description, and drawing conclusions from the data obtained. The results showed that the lesson planning was not in line with the lesson plan (RPP) that had been prepared previously. This is mainly due to the limited learning aids provided by the school, which are inadequate in supporting the learning process. In addition, teachers also face limited time constraints in implementing learning. In the learning process, the lecture method is widely used by teachers, and the use of learning aids is limited. Time constraints also affected the implementation of learning practices, so not all learning materials regarding talempong pacik music could be taught thoroughly. The results showed that learning has not fully provided satisfactory results. Although teachers try to give their best to learners and maintain their enthusiasm for learning, learners still seem to have difficulties in participating in learning, especially in the practice of traditional music.